Peramalan Status Siaga Banjir Berdasarkan Data Curah Hujan (ARR) dan Tinggi Muka Air (AWLR) Menggunakan Metode Fuzzy Time Series (Studi Kasus: Perum Jasa Tirta I) - Arina Rufaida; Muhammad Tanzil Furqon; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Flood is a condition where water flow is higher than normal water level so it flooded the surrounding area. Floodwaves flow from upstream to downstream and interact with increasing water capacity of the estuary. Floods can occur due to high rainfall, overflow from the river, the destruction factor of Watershed (DAS). From that point on, a system that is able to forecast to make it easier to analyze the flood alert status in the future. Regression method used in this research is Fuzzy Time Series. The FTS method is a model usually used to forecast data in sequence. This research has a goal to forecast flood alert in Kambing Station DAS Brantas . The results of the test show the prediction of flood alert on the water level data (AWLR) that is in December 2016 got the error value (RMSE) of 2.89 and rainfall data (ARR) in February 2015 got the error value (RMSE) of 16.0. Both data resulted flood alert forecasting that shows Normal.